Restoration of white-backed woodpecker Dendrocopos leucotos habitats in central Sweden - Trogen, Niklas (2015)
During the last century Swedish forestry has developed to become one of the most advanced and intensive in the world. During this development many forest living species have suffered from habitat loss, for example the white-backed woodpecker Dendrocopos leucotos L. One of the forest companies in central Sweden, Bergvik Skog, is currently restoring habitats for this umbrella species by favoring deciduous trees and by creating dead wood. The aim of this study was to simulate the development of stands restored for the woodpecker. I simulated four scenarios for 100 years into the future: 1) free development of restored stands, 2) free development of control stands (i.e. unrestored), 3) thinning of spruce when it reaches 5% of the growing stock in restored stands and 4) management for timber production in control stands. The results show that the goals set by Bergvik Skog (maximum and minimum proportion of Norway spruce Picea abies L. trees and deciduous trees, respectively, and minimum volume of dead deciduous wood) can be achieved during most of the 100-year period under the spruce thinning scenario for restored stands. A threshold of 8 m3/ha deciduous snag (used to indicate good white-backed woodpecker habitat) was only reached in two out of five stands during the last 20-45 years of the study period. When studying the biodiversity indicators dead wood volume, proportion of deciduous trees and density of large trees, different scenarios had different effects on the indicators. The main conclusions of the study are 1) the goals set by Bergvik Skog can be reached if the right management is chosen, 2) to reach the deciduous snag threshold one must probably use other methods than the ones simulated in this study and 3) the different scenarios had different effects on the biodiversity indicators and they must thus be chosen with consideration of the specific conservation goals of interest.